PENERAPAN PEMBELAJARAN BERDIFERENSIASI BERBASIS KEBUTUHAN BELAJAR UNTUK MENINGKATKAN HASIL BELAJAR GULING DEPAN SENAM LANTAI PADA SISWA SMP KELAS VII - Ronal Widianto; Muhammad Yahya Mubarok; Rizjal Affan Fauzi; Fifukha Dwi Khory; Ifanuddin Muchtar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Differentiated learning is learning that provides flexibility and is able to accommodate students' needs to increase their potential according to students' different learning needs, interests and learning profiles. The aim of this research is to improve learning outcomes for forward roll by implementing differentiated learning in PJOK subjects. This research uses a classroom action research method carried out in two cycles starting from pre-cycle activities. Each cycle is carried out starting from planning, implementation, observation, evaluation and reflection activities. This research was conducted at SMPN 28 Surabaya in class VII-E with a total of 34 research subjects. The research instrument uses an assessment of the skill aspect in the floor exercise material, namely the front roll. Using an assessment rubric sheet with an assessment grid that has a KKM score of 80 which is the student's learning completeness. Data analysis uses descriptive statistics and percentage results test. As for the results of the pre-cycle research, 4 students (12%) completed 30 students (88%) with an average score of 61.6. In cycle I there was an increase with the number of 14 students (41%) completing and 20 students (59%) not completing with an average score of 76.6. In cycle II there were 32 students (94%) who completed, 2 students (6%) did not complete with an average score of 84.3. It can be concluded that the differentiation learning strategy can improve student learning outcomes related to forward rolling in floor exercise.